The Use of Social Media as a Digital Nutrition Education Tool: Interactive Strategies for Teenagers (Journal Nutrizione, 2025)
The increasing use of digital technology among adolescents has encouraged the development of social media as an alternative medium for nutrition education. Adolescents, as active users of digital platforms, interact intensively in virtual spaces, making social media a potential channel for delivering health information in an engaging, accessible, and adaptable format. This study analyzes the role of social media as a digital tool for nutrition education and explores effective interactive strategies to improve adolescents’ knowledge, attitudes, and healthy eating behaviors. A literature review of recent studies from various scientific databases shows that platforms such as Instagram, TikTok, YouTube, and WhatsApp serve as attractive educational media due to their visual features, ease of access, and support for two-way communication. Several effective interactive strategies were identified, including multimedia-based content, gamification, microlearning, live discussions, and the use of health influencers. The findings indicate that social-media-based interventions can enhance engagement, broaden information reach, and promote positive behavior change when designed with a participatory, culturally relevant, and consistent approach. This study underscores the importance of integrating digital technology into adolescent health promotion programs and offers recommendations on interactive strategy models that can be implemented by health practitioners, educators, and policymakers. Overall, these insights contribute to the development of adaptive nutrition education practices aligned with adolescents’ characteristics in the digital era.